Epidemiological and serological aspects of hepatitis A among children and teenagers in the city of Santos: a cross-sectional study - Ciaccia, Maria Célia Cunha; Moreira, Regina Célia; Ferraro, Alexandre Archanjo; Lemos, Marcílio Figueiredo; Oba, Isabel Takano; Porta, Gilda (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: Viral hepatitis A is still a concern at public health level in Brazil and around the world, due both to the number of affected subjects and the possibility of complications in the acute forms. The Brazilian Ministry of Health estimates that at least 70% of this country’s population has already had contact with the hepatitis A virus (HAV). The aim here was to discover the prevalence of serological markers for the hepatitis A virus among children and teenagers at daycare facilities, kindergartens and elementary schools in the city of Santos. DESIGN AND SETTING: Cross-sectional study in kindergartens and elementary schools within the municipal education network in several regions of the city of Santos. METHOD: Students’ family members were surveyed using a questionnaire and 4,680 finger-prick blood samples were taken and assayed by means of the ELISA technique. RESULTS: The general prevalence of anti-HAV IgG was 9.72% and, of these cases, 74.6% were reactive to antiHAV IgM. There was higher prevalence of anti-HAV IgG among older children, females, children who played in streams, those whose homes were not connected to the sewage system, those whose parents had low education levels, those with low household income and those who did not live along the seashore. The prevalence of anti-HAV IgM peaked in the early years and subsequently fell, and it was lower on the hills and in the Northwestern Zone. CONCLUSION: The general prevalence of serological markers for hepatitis A was low in Santos.